Private service provision contributes to widespread innovation adoption among smallholder farmers: Laser land levelling technology in northwestern India - Subash Surendran Padmaja; Martin Christoph Parlasca; Matin Qaim; Vijesh V. Krishna (University of Bonn, Center for Development Research (ZEF), 2024)
This study investigates key institutional factors promoting the adoption of laser land levelling (LLL), a technology that has gained wide popularity among farmers in northwestern India despite being indivisible. The main objective is to evaluate the role of service providers, offering LLL on a rental basis to farmers, for technology dissemination among smallholders with fragmented plots. Plot-level data from 1,661 households across 84 villages in Punjab and western Uttar Pradesh in India were collected and used to analyse farmers' LLL technology perceptions and adoption decisions. Regression models were developed to estimate the role of local service provision for LLL adoption while controlling for farm, household, and other contextual variables. The analysis pays particular attention to the heterogeneous effects of service provision on farmers with different farm and plot sizes. The data and estimates reveal that local access to a larger number of service providers is associated with higher rates of LLL adoption among farmers. The effect of service providers on adoption varies by farm and plot size: it is larger on smaller farms/plots. The findings suggest that a conducive institutional environment that accommodates the specific needs of different farm sizes can speed up innovation adoption. This finding makes a case for re-evaluating traditional agricultural technology scaling models to include individual service provision for broader and more inclusive adoption.
Keywords: O13; Q15; Q16; Q18; 330; Adoption; Smallholder farmers; Agricultural machinery; Indivisible agricultural technology